On Aristotle’s arguments for the Earth’s smallness: argumentative gaps and context - L. Recio, Gonzalo (Circumscribere International Journal for the History of Science, 2022)
In the last chapter of the second book of his De Caelo, Aristotle argues for the Earth’s smallness. In this paper I will differentiate between three relevant ways in which this feature can be understood, and I will explain how Aristotle’s arguments relate to them. I will argue that Aristotle’s arguments, as they are presented in the relevant passages, are not conclusive, and finally I will provide a plausible context which might help understand Aristotle’s text.